Comparing 2-day vs 3-day flu-CY lymphodepleting regimens for CD19 CAR T-cell therapy in patients with non-hodgkin’s lymphoma - Frame, David G.; Geer, Marcus; Kasha, Salena; Markstrom, Denise; Scappaticci, Gianni; Feeney, Tate; Hayduk, Andrew; Mansoor, Hilary M.; Oberfeld, Avery; D’Antonio, Hannah; Anand, Sarah; Choi, Sung Won; et al. (Frontiers in Immunology, 2024)
Lymphodepleting chemotherapy (LDC) is critical to improving CAR T-cell expansion and efficacy. Despite this, there is not a consensus in the literature regarding the optimal LDClymphodepleting chemotherapy regimen, including dose and frequency.We retrospectively reviewed consecutive patients at a single institution that received LDClymphodepleting chemotherapy prior to treatment with the CD19 directed CAR T-cell products axicabtagene ciloleucel and tisagenlecleucel at a single institution. Patients treated at our center received fludarabine 30 mg/m 2 and cyclophosphamide 500 mg/m 2 fludarabine for 3 consecutive days prior to May 2019. After this timepoint patients routinely received fludarabine 40 mg/m 2 and cyclophosphamide 500 mg/m 2 for 2 consecutive days. Clinical data from each cohort were obtained from the electronic medical record and compared for differences in CAR T-cell efficacy and toxicity.From June 2018 to August 2023, LDClymphodepleting chemotherapy was given to 92 patients prior to CD19 directed CAR T-cell therapy for relapsed non-Hodgkin's lymphoma. Twenty -eight patients received a 3-day regimenregimen, and 64 patients received a 2-day regimen. In the total cohort, 7581% of patients received axicabtagene ciloleucel and 2519% received tisagenlecleucel. The overall response rates in both the 2-day regimen group and the 3-day regimen group were similar (697% vs 759%, p= 0.2133) as was were the complete response rates (502% vs 54%, p=0.82). There were no significant differences between the 2-day and 3-day regimens for grade 2-4 cytokine release syndrome (55% vs 50%, p=0.82), grade 2-4 immune effector cell associated-neurotoxicity syndrome (42% vs 298%, p=0.25), or time to resolution of neutropenia or thrombocytopenia. The Rrates of prolonged platelet recovery lasting greater than 60 days were was higher with the 3-day regimen (9% vs 27%, p=0.026).(17% vs 39%, p=0.03).As the number of patients eligible for CAR T-cell therapy continues to increase, optimizing each component of therapy is necessary. We show that a 2-day regimen of LDClymphodepleting chemotherapy with fludarabine and cyclophosphamide is feasible without significant impact on CAR T-cell efficacy or toxicity. Prospective studies are necessary to further determine the most effective LDC regimen.